GAMBARAN MOTIVASI BELAJAR PADA SISWA SMP PGRI 1 CIANJUR - Imas Masroh Nurasiah; Heris Hendriana; Ecep Supriatna (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
This study aims to describe the learning motivation of junior high school students in Cianjur. Learning motivation has an important role for every student to have. This research method uses quantitative description. In this study, data was collected by filling out a questionnaire containing 26 statements carried out by 120 class VIII students. Based on the results of the study showed that the description of the learning motivation of the students of SMP PGRI 1 Cianjur was in the medium category. Which means that students are in the middle between the high and low categories, at this time students have enough ability and can be motivated to learn. For the results of the research presented in the form of a diagram depicting learning motivation, the results obtained are that 15% of students are low in the aspect of perseverance in learning, 73% of students are interested in learning and 12% of students are high in tenacity in learning. The results of this study are to determine the description of learning motivation that must be considered in helping to increase student motivation to learn. Keywords: : Learning Motivation, Students